Recurrence pattern in patients with a pathologically complete response after neoadjuvant chemoradiotherapy and surgery for oesophageal cancer1. Issue 2 (23rd November 2012) - van Hagen, P.; Wijnhoven, B. P. L.; Nafteux, P.; Moons, J.; Haustermans, K.; De Hertogh, G.; van Lanschot, J. J. B.; Lerut, T.
Abstract Background: Little is known about recurrence patterns in patients with a pathologically complete response (pCR) or an incomplete response after neoadjuvant chemoradiotherapy (CRT) followed by resection for oesophageal cancer. This study was performed to determine the pattern of recurrence in patients with a pCR after neoadjuvant CRT followed by surgery. Methods: All patients who received neoadjuvant CRT followed by oesophagectomy between 1993 and 2009 were identified from a database, and categorized according to pathological tumour response. Recurrences were classified as locoregional or distant. Results: One hundred and eighty‐eight patients were included. Median potential follow‐up was 71·6 months. A pCR was achieved in 62 (33·0 per cent) of 188 patients. Recurrence developed in 24 (39 per cent) of 62 patients with a pCR and 70 (55·6 per cent) of 126 without a pCR (P = 0·044). Locoregional recurrence with or without synchronous distant metastases occurred in eight patients (13 per cent) in the pCR group and 31 (24·6 per cent) in the non‐pCR group (P = 0·095). Locoregional recurrences without synchronous distant metastases occurred four (6 per cent) and ten (7·9 per cent) patients respectively (P = 0·945). The overall 5‐year survival rate was significantly higher in the pCR group than in the non‐pCR group (52 versus 33·9 per cent respectively; P = 0·019). Conclusion: Of patients with a pCR, 13 per cent still developed a locoregional recurrence. Although pCR is more favourable for survival, it is not synonymous with cure or complete locoregional disease control. Copyright © 2012 British Journal of Surgery Society Ltd. Published by John Wiley & Sons, Ltd.